Analisis Nilai Perusahaan Consumer Goods Yang Terdaftar di Bursa Efek Indonesia - Eddy Priyanto (CV. ULIL ALBAB CORP, 2023)
The purpose of this research is to determine the influence of leverage, liquidity and investment variables on the value of companies in the consumer goods sector on the Indonesian Stock Exchange. The population of this research is all consumption sector companies listed on the Indonesian Stock Exchange. In this research, the sampling method used was purposive sampling, which obtained 35 consumer goods sector companies registered on the IDX which can be used as research data. The data analysis technique uses multiple linear regression analysis with the SPSS 20.00 application. The research results show that leverage and liquidity have no influence on company value. Meanwhile, investment has a positive and significant effect on the value of consumer goods sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period.